2022
DOI: 10.3390/polym14081532
|View full text |Cite
|
Sign up to set email alerts
|

Kraft Lignin/Tannin as a Potential Accelerator of Antioxidant and Antibacterial Properties in an Active Thermoplastic Polyester-Based Multifunctional Material

Abstract: This research focuses on key priorities in the field of sustainable plastic composites that will lead to a reduction in CO2 pollution and support the EU’s goal of becoming carbon neutral by 2050. The main challenge is to develop high-performance polyphenol-reinforced thermoplastic composites, where the use of natural fillers replaces the usual chemical additives with non-toxic ones, not only to improve the final performance but also to increase the desired multifunctionalities (structural, antioxidant, and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 65 publications
3
7
0
Order By: Relevance
“…By contrast, the addition of either L or NL in the PLA matrix enhanced the antioxidant activity, as could be deduced from the higher reduction rate of DPPH• over time. The composites with higher L/NL content showed better antioxidant activity, in agreement with the literature [ 30 , 43 , 74 ]. In the case of the PLA–L composites, the PLA–L composite with 5 wt% L loading yielded 74% residual DPPH content reduction after 8 h, while the PLA–L composites with lower L loadings (0.5–2.5 wt%) showed poor antioxidant activity.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…By contrast, the addition of either L or NL in the PLA matrix enhanced the antioxidant activity, as could be deduced from the higher reduction rate of DPPH• over time. The composites with higher L/NL content showed better antioxidant activity, in agreement with the literature [ 30 , 43 , 74 ]. In the case of the PLA–L composites, the PLA–L composite with 5 wt% L loading yielded 74% residual DPPH content reduction after 8 h, while the PLA–L composites with lower L loadings (0.5–2.5 wt%) showed poor antioxidant activity.…”
Section: Resultssupporting
confidence: 91%
“…In addition, PLA–L films showed excellent antimicrobial activity, reducing the viability of Gram-positive bacteria tenfold. Similar results were obtained by Cresnar et al [ 30 ] and by Domenek et al [ 31 ], who prepared PLA–L films by melt-mixing using Kraft and Soda lignin, respectively. Both studies also reported greater antioxidant activity with increasing lignin content.…”
Section: Introductionsupporting
confidence: 89%
“…The visual appearance of the films prepared by compression moulding ( Figure 2 ) shows a macroscopically uniform distribution of the lignin in the PLA matrix without any visible particles or aggregates. In contrast, the PLA/kraft lignin composites, prepared without the use of masterbatch directly in the melt compounder, resulted in a visibly heterogenous polymer [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…In previous work, by our group, kraft lignin was added to a PLA matrix, via melt mixing, and the composites had both antioxidant and antibacterial activity, an increased hardness and Young’s modulus, accelerated crystallization, and a slightly improved thermal stability [ 14 , 15 , 16 ]. In this work, another type of biorefinery lignin, the so-called organosolv lignin, was evaluated as a filler in PLA.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Pušnik et al studied the changes in surface properties, antibacterial activity, and mechanical properties of PLA films by adding metal-based nanoparticles, namely, Ag, ZnO, and TiO 2 [ 38 ]. In another work by the same group, the improvement of properties was investigated by the addition of wood fibres, kraft lignin and tannin [ 43 ]. Giulia Fredi et al demonstrated successfully that mixing PLA with different poly(alkylene furanoates) would improve the mechanical properties and gas barrier properties, making it more suitable for packaging [ 44 ].…”
Section: Basic Packaging Materialsmentioning
confidence: 99%